2019
DOI: 10.1186/s13075-019-1953-4
|View full text |Cite
|
Sign up to set email alerts
|

High baseline fat mass, but not lean tissue mass, is associated with high intensity low back pain and disability in community-based adults

Abstract: Objectives Low back pain is the largest contributor to disability worldwide. The role of body composition as a risk factor for back pain remains unclear. Our aim was to examine the relationship between fat mass and fat distribution on back pain intensity and disability using validated tools over 3 years. Methods Participants (aged 25–60 years) were assessed at baseline using dual-energy X-ray absorptiometry (DXA) to measure body composition. All participants completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 57 publications
0
39
1
Order By: Relevance
“…Association of MSP manifestations with body composition characteristics were also repeatedly reported [ 30 , 31 , 32 , 33 ]. Body mass index (BMI) and other anthropometric measures of obesity were found to be associated with LBP intensity in both men and women [ 34 , 35 , 36 ], suggesting the involvement of AT in LBP pathogenesis. However, in these studies, the peripheral levels of adipokines that can potentially serve as the peripheral molecular LBP biomarkers, have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Association of MSP manifestations with body composition characteristics were also repeatedly reported [ 30 , 31 , 32 , 33 ]. Body mass index (BMI) and other anthropometric measures of obesity were found to be associated with LBP intensity in both men and women [ 34 , 35 , 36 ], suggesting the involvement of AT in LBP pathogenesis. However, in these studies, the peripheral levels of adipokines that can potentially serve as the peripheral molecular LBP biomarkers, have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Another found that higher levels of fat mass deposition around the hips were weakly related to increases in the prevalence of CLBP in women through the investigation of 1,128 female twins [13]. There exists evidence on the important role of fat mass, speci cally android fat relative to gynoid fat, in back pain and disability [11]. We found that the total fat mass relative to the total body weight did not differ by CLBP status, except in men with obesity; however, people with CLBP and obesity had a higher fat distribution in the lower limbs than those without CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have focused on the association of fat mass distribution with LBP. Brady et al provided evidence on the crucial role of fat mass, especially android fat relative to gynoid fat, in back disability and pain [11]. While Hussain et al showed that LBP-induced pain intensity and disability were related to body composition measures, such as fat mass, fat proportion, and waist circumference, they did not include su cient information on the manner in which regional fat distribution is associated with LBP [12].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, it would be convenient to increase the sample size of the study, so that stratification by spine sector, age, and gender was effective in all subgroups and had adequate statistical power. In addition, it would have been helpful to have included body mass index values in the study, since being overweight and/or obese are factors that can influence back pain, especially in the lumbar area (42,43).…”
Section: Limitationsmentioning
confidence: 99%